2021
DOI: 10.3390/s21217222
|View full text |Cite
|
Sign up to set email alerts
|

Handheld Multispectral Fluorescence Imaging System to Detect and Disinfect Surface Contamination

Abstract: Contamination inspection is an ongoing concern for food distributors, restaurant owners, caterers, and others who handle food. Food contamination must be prevented, and zero tolerance legal requirements and damage to the reputation of institutions or restaurants can be very costly. This paper introduces a new handheld fluorescence-based imaging system that can rapidly detect, disinfect, and document invisible organic residues and biofilms which may host pathogens. The contamination, sanitization inspection, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 26 publications
(34 reference statements)
0
16
0
Order By: Relevance
“…In addition, the size limit of detectable contaminant was determined to be about 0.15 mm for a single colony on an agar plate. Similarly, Sueker et al [ 28 ] reported that the minimum detectable spot size for saliva and respiratory droplets on stainless steel plates was about 0.13 mm, using a CSI-D device (a previous model of CSI-D+). These limitations, such as detectable concentrations or spot size, are also affected by the measurement parameters, such as working distance and angle of incidence of the excitation light.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition, the size limit of detectable contaminant was determined to be about 0.15 mm for a single colony on an agar plate. Similarly, Sueker et al [ 28 ] reported that the minimum detectable spot size for saliva and respiratory droplets on stainless steel plates was about 0.13 mm, using a CSI-D device (a previous model of CSI-D+). These limitations, such as detectable concentrations or spot size, are also affected by the measurement parameters, such as working distance and angle of incidence of the excitation light.…”
Section: Discussionmentioning
confidence: 96%
“…Some systems focus on the disinfection of individual items within a container or room, while others are designed to irradiate large areas of interest with multiple UV bands. Ideally, these systems should provide disinfection capability with multiple bands while maintaining portability [ 28 ]. A recent report utilizing the CSI-D+ device (also used in this study) demonstrated simultaneous fluorescence-based detection and UV-based sterilization capability in a single battery-operated unit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we have demonstrated detection of invisible human saliva and respiratory droplets on stainless steel and plastic surfaces 22 . A secondary capability is to provide immediate spot disinfection using the UVC germicidal effect when residual contamination is discovered during audits.…”
Section: Introductionmentioning
confidence: 93%
“…In this study, we employ a fluorescence imaging device developed by SafetySpect and two state-of-the-art deep learning algorithms, including EfficientNet and U-Net, to first discriminate the video frames with fecal residue on meat surfaces and then accurately segment and identify the corresponding areas of fecal contamination in the image. The handheld automated imaging inspection device (CSI-D), created by SafetySpect 13 , offers mobility and flexibility for fluorescence-based contaminant detection on both food products (e.g., carcasses) and equipment surfaces in meat processing facilities under bright ambient light. Visualization by fluorescence emission has excellent potential for food safety procedures.…”
Section: Introductionmentioning
confidence: 99%